Combating the threats of cybercrimes in Malaysia: the efforts, the cyberlaws and the traditional laws - Mohamed, Duryana (Elsevier Ltd., 2013)
Cybercrimes are increasing in Malaysia. According to a report the crimes jumped by 88 percent in 2011 with 15,218 cases compared with 8090 in 2010. This report has caused a lot of concern from the Government and the public. At a glance, these crimes are like ‘diseases’spreading throughout the country and causing damage to people, the economy and the country. Although various efforts have been taken and some are still ongoing, total prevention of cybercrime is very difficult. Combating the threat is very challenging since Malaysia is still lacking in many of the tools required including manpower and technology. But the efforts will continue. This paper discusses some of the efforts taken by the Government and other organisations to deal with these problems followed by an analysis on the application of cyberlaws and how these measures work together with the traditional law in tackling cybercrime cases.